Characteristics and sources of hourly elements in PM10 and PM2.5 during wintertime in Beijing. (1st June 2021) - Rai, Pragati; Furger, Markus; Slowik, Jay G.; Zhong, Haobin; Tong, Yandong; Wang, Liwei; Duan, Jing; Gu, Yifang; Qi, Lu; Huang, Ru-Jin; Cao, Junji; Baltensperger, Urs; et al.
Abstract: Characteristics and sources of ambient particle elements in urban Beijing were studied by hourly observations in two size fractions (PM10 and PM2.5 ) during November and December 2017 using an online multi-element analyzer. The reconstructed oxide concentrations of 24 elements (from Al to Pb) comprise an appreciable fraction of PM10 and PM2.5, accounting for 37% and 17%, respectively on average. We demonstrate the benefit of using high-time-resolution chemical speciation data in achieving robust source apportionment of the total elemental PM10 (PM10el ) and elemental PM2.5 (PM2.5el ) mass using positive matrix factorization (PMF). Biomass burning, coal combustion, secondary sulfate, industry, non-exhaust traffic and dust were identified in both size fractions (with varying relative concentrations), which accounted on average for 4%, 12%, 5%, 2%, 14%, and 63%, respectively to the total PM10el, and 14%, 35%, 21%, 6%, 12% and 12%, respectively to the total PM2.5el . Biomass burning and coal combustion exhibited higher concentrations during haze episodes of the heating season. In contrast, secondary sulfate and industry contributed more to haze episodes during the non-heating season. The fractional contribution of dust was mostly high during clean days, while the fractional non-exhaust traffic emission contribution was similar throughout the measurement period. The non-exhaust traffic emissions contributed locally, while the remaining sources were dominated by neighboring areas. Furthermore, trajectory analysis showed that the origin of the industrial sources roughly agreed with the locations of the main point sources. Overall, this work provides detailed information on the characteristics of the elements during different haze events during heating and non-heating seasons. Graphical abstract: Image 1 Highlights: Quantified highly time-resolved elements in PM10 and PM2.5 in Beijing. Reconstructed oxides concentrations of elements amounted to 37% and 17% of the total PM10 and PM2.5 mass, respectively. Coal combustion was predominant in haze episodes during the heating season. Southwestern and southern domains were the most influential source regions.